Case report: two case reports of the effect of repetitive peripheral magnetic stimulation on pharyngeal dysphagia - Sukpongthai, Thanyaphon; Charussuriyong, Paveenrath; Suksathien, Rachawan (Journal of Thai Stroke Society, 2024)
Dysphagia is a common sequela after a stroke, significantly impacting the overall recovery outcome. Complications associated with poststroke dysphagia, such as aspiration pneumonia, dehydration, malnutrition, and, in some cases, death, highlight the importance of screening and proper management as essential tools. This study aims to evaluate the effectiveness of repetitive Peripheral Magnetic Stimulation (rPMS) intervention in the pharyngeal dysphagia stage. Two cases of poststroke dysphagia were recruited for treatment, with a frequency of 20 Hz and 35% intensity, for a total of 1,200 pulses per session twice per week and a total of 16 sessions. Changes in the Eating Assessment Tool-10 (EAT-10) score and the Functional Oral Intake Scale (FOIS) level were recorded, showing improvement in both parameters. As a result, the patients could remove the nasogastric (NG) tube and resume an oral diet with the assistance of swallowing maneuvers. The findings suggest that rPMS may be beneficial for addressing pharyngeal stage dysphagia.